Strengthening Health Systems for Persons With Traumatic Spinal Cord Injury in South Africa and Sweden: A Protocol for a Longitudinal Study of Processes and Outcomes - Conradsson, David; Rhoda, Anthea; Mlenzana, Nondwe; Nilsson Wikmar, Lena; Wahman, Kerstin; Hultling, Claes; Joseph, Conran (Frontiers in Neurology, 2018)
Background: The provision of specialized care in a time-sensitive manner has shown to be crucial for survival and recovery of functioning after a traumatic spinal cord injury (TSCI). However, little is known about the provision of TSCI care in different international contexts; information which is required for strengthening policy and practice. Aims: The overarching aim of this study will be to explore health care processes and outcomes of TSCI care in South Africa and Sweden. Specific aims will be to: 1) describe acute processes of TSCI care, 2) determine acute- and long-term outcomes of TSCI care and 3) identify predictors for survival, secondary complications and functioning 12 months post-injury. Methods: A prospective (regional), population-based cohort study where adults with an acute TSCI will be recruited over at least a one-year period from the City of Cape Town, South Africa, and Stockholm, Sweden. The anticipated sample size inclusive of both international contexts will be 200 participants − based on a power calculation for detecting differences in mortality. Information on the nature and timing of processes of acute care (e.g. transfer logistics, spinal surgery and specialized SCI care) will be collected on acute care admission and discharge using a standardized form. Survival status, secondary complications, neurological symptoms, functional status, activity and participation as well as health-related quality of life will be collected at discharge from SCI acute care and at 12-months post-injury. Secondary complications and functioning will be compared between South Africa and Sweden using inferential statistics. To address mortality specifically, the indirect standardization method for differences in mortality between contexts will be used whereby Stockholm will serve as standard for international care. For the assessment of factors related to mortality and other outcomes (e.g. neurological and secondary health conditions) multivariate regression analyses will be used to determine independent risk factors. Conclusion: This study offers a unique investigation of the relationship between health care processes and outcomes of TSCI care with the aim of strengthening management guidelines for SCI in South Africa and Sweden.